2009
DOI: 10.1159/000295002
|View full text |Cite
|
Sign up to set email alerts
|

Skinks (Reptilia: Scincidae) Have Highly Conserved Karyotypes as Revealed by Chromosome Painting

Abstract: Skinks represent the most diversified squamate reptiles with a great variation in body size and form, and are found worldwide in a variety of habitats. Their remarkable diversification has been accompanied by only a few chromosome rearrangements, resulting in highly-conservative chromosomal complements of these lizards. In this study cross-species chromosome painting using Scincus scincus (2n = 32) as the source genome, was used to detect the chromosomal rearrangements and homologies between the following skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 63 publications
7
33
0
Order By: Relevance
“…Cross-species painting between these species has been very informative, although the hybridization efficiency has been less than in birds or mammals: this is understandable in view of the longer divergence times. The results are consistent with greater genome conservation and even fewer evolutionary rearrangements than in birds [Giovannotti et al, 2009;.…”
Section: Chromosome Paints Have Been Made Recently In the Cambridge Lsupporting
confidence: 78%
“…Cross-species painting between these species has been very informative, although the hybridization efficiency has been less than in birds or mammals: this is understandable in view of the longer divergence times. The results are consistent with greater genome conservation and even fewer evolutionary rearrangements than in birds [Giovannotti et al, 2009;.…”
Section: Chromosome Paints Have Been Made Recently In the Cambridge Lsupporting
confidence: 78%
“…Most studies based on karyological analyses (Kupriyanova, 1986;Caputo et al, 1993Caputo et al, , 1994 and morphological/molecular studies (Carranze et al 2008) showed the paraphyly of E.schneiderii group species and argued that Scincus may be derived from an E. schneiderii-like stock. The Scincus Eumeces clade considered basal to other members of the family (Giovannotti et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Such experiments have been successfully performed for comparative cytogenetic studies in mammals, birds, reptiles, and fishes [e.g. Reed et al, 1995;Yang et al, 1995Yang et al, , 1999Yang et al, , 2003Griffin et al, 1999;Campos-Ramos et al, 2001;Phillips et al, 2001;Rens et al, 2001Rens et al, , 2003Rens et al, , 2004Rens et al, , 2006Harvey et al, 2002;Liu et al, 2002;Guttenbach et al, 2003;Grützner et al, 2004;Nanda et al, 2006Nanda et al, , 2007Nanda et al, , 2008Ferguson-Smith and Trifonov, 2007;Henning et al, 2008;Giovanotti et al, 2009;Cioffi et al, 2013]. Previous cytogenetic studies on NORs in Anura clearly demonstrate that the overwhelming majority of species possess only a single 'standard' pair of NORs [Schmid, 1980;King, 1990;Green and Sessions, 2007;Schmid et al, 2010Schmid et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%